Synthesis and Characterization of New Schiff bases Derivatives of Acetohydrazide and its Cyclization Reaction - Mustafa M. Shihab (Journal of Global Pharma Technology, 2016)
This work includes synthesis of hydrazide from 5-Amino-1, 3, 4-thiadiazole-2-thiol. Also reaction of hydrazide with different aromatic aldehydes by using glacial acetic acid as catalyst to synthesis of some new Schiff bases derivatives that coupled with thioglycolic acid to synthesis five- member ring heterocyclic compounds derivatives containing thiazolidinone ring. All synthetic compounds were definite by their melting point, FT-IR spectra and 1H-NMR spectra for some of them.Keywords: 5-Amino-1, 3, 4-thiadiazole-2-thiol, thiazolidinone, Schiff bases, Heterocyclic compounds, Thiadiazole.